The role of perceived organizational support and person-organization fit in the relationship between corporate social responsibility and work engagement - Duarte, A.P.; Neves, J.; Ribeiro, N. (X Postgraduate Conference Management, Hospitality & Tourism, 2019)
Previous research suggests that corporate social responsibility (CSR), that is, the attention given by organizations to the integration of social and environmental concerns in their business activities, has influence on diverse job-related attitudes and behaviors. Following this line of research, the present study aimed to analyze the relationship between employee perceptions of CSR and work engagement, within the scope of a research model that proposes perceived organizational support and person-organization fit as potential psychological mediators.For testing the research model, a correlational study was developed. Data were collected through an electronic survey, being the participation in the study voluntary and anonymous. 168 employees of organizations operating in Portugal completed the survey which included measures of the main variables selected from the literature. Data were analyzed using PROCESS macro for IBM SPSS 22.0. The results indicate that employees' perception of the level of involvement of their employer in CSR practices has a direct positive effect on their levels of work engagement. The more responsible the organization is considered, the more vigorous, dedicated and absorbed the employees becomes in their daily work. This effect is mediated by the proposed variables, which suggests that the involvement in socially responsible practices contributes to a greater perception of both organizational support and person-organization fit, which subsequently promote higher levels of engagement at work.